In Vitro Technologies for American Chestnut (Castanea dentata (Marshall) Borkh) Conservation - Zhuoya Liu; Wen-Lu Bi; Mukund R. Shukla; Praveen K. Saxena (Plants, 2022)
American chestnut (Castanea dentata), a native species of eastern North America, is an economically important deciduous hardwood tree that has been designated as endangered in Canada. The population of American chestnut trees has dwindled significantly across Southern Ontario due to chestnut blight and many of the surviving trees continue to show blight disease symptoms. American chestnut requires efficient strategies for propagation and preservation for species recovery. The objective of this study was to develop a long-term plant conservation program using micropropagation and cryopreservation protocols. An in vitro technology using a liquid-based temporary immersion system (TIS) was developed for micropropagation of American chestnut. The highest rate of shoot multiplication was observed in cultures grown in the DKW (Driver and Kuniyuki 1984) basal medium supplemented with 2.2 µM 6-benzylaminopurine and 1.0 µM gibberellic acid. More than 95% of proliferated microshoots, about 40–50 mm in size, developed roots after 30 days of culture within bioreactor vessels containing DKW basal medium supplemented with 15 µM 3-Indolebutyric acid. Rooted plantlets transplanted to the greenhouse had a survival efficiency of 82% after one month of growth. The cryopreservation protocol for germplasm preservation was developed through droplet vitrification of shoots. Optimal regeneration of shoot tips occurred from explants precultured on stepwise concentrations of sucrose and subsequent dehydration in PVS3 for 30 min. Cryopreserved shoot tips were regenerated to whole plants using pre-optimized conditions of micropropagation. This study confirms the potential of TIS for micropropagation in ex situ conservation and reintroduction of endangered American chestnuts and possibly other woody plant species.